Analisis Kontribusi Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Pertumbuhan Ekonomi: Studi pada Kabupaten Sampang dengan Belanja Daerah Sebagai Variabel Intervening - Siti Rohizah; Kiky Asmara; Fauzatul Laily Nisa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Economic development in a region is one of the starting points in the implementation of development with the hope that the region can find out the potential that exists in order to utilize it to fulfill the needs in the region. Sampang Regency still has problems and challenges in regional financial management. Balance funds are still the main source of regional income with an increasing value. This study aims to analyze the effect of Regional Original Revenue and Balancing Funds on Economic Growth with Regional Expenditure as an intermediary variable that is considered to be able to connect between variables. With the quantitative analysis method and path analysis technique, the results show that Local Revenue has a negative and insignificant effect on Economic Growth, while the Balance Fund variable has a positive and significant effect on Economic Growth. Furthermore, the Regional Expenditure variable cannot mediate the relationship between Local Revenue and Economic Growth because it still produces a negative value, on the other hand, Regional Expenditure is able to become an effective intervening variable in the relationship between balancing funds and economic growth.